A peacock in the land of penguins : a fable about creativity and courage - Gallagher, B. J. (Barbara J.), 1949- (BK business book., 2015)
"This is a book for everyone who wishes to contribute their unique gifts to the world."--Archbishop Desmond Tutu, Nobel Peace Laureate This brand new edition of a classic, international bestseller continues to bring keen insight to an important topic--workforce diversity. Written in a charming, engaging style, it is a contemporary corporate fable--a tale for our times. This special 20th anniversary edition includes many new tips, tools, and strategies for peacocks and penguins alike--as well as an entirely new bonus parable. Through the story of Perry the Peacock and his fine feathered friends, authors Gallagher and Schmidt bring to life the challenges of birds of different feathers who struggle to be successful in the conformity-minded Land of Penguins. Their travails illuminate the challenges of creating a pluralistic corporate culture in which the talent, energy, and commitment of all employees are fully engaged. People who have new ideas that differ from business as usual are often ignored or criticized for the very thing that makes them valuable: their originality and creativity. This unique book helps organizations break out of penguin thinking" in order to tap into and leverage the creativity of diversity. Learn how to cultivate an organizational culture in which new ideas can flourish and innovation can take flight